Prosthetic Valve Endocarditis: A Case Report - Huque, AKM Ziaul; Khan, Omar Sadeque; Shah, Sanjeet Kumar; Aftabuddin, Md; Adhikary, Asit Baran; Morshed, Nahid Mahjabin (University Heart Journal, 2017)
Prosthetic valve endocarditis(PVE) is the most serious complications of valve replacement. Despite improvements in medical treatment and surgery, prosthetic valve endocarditis carries a high mortality. The best treatment strategy for these patients is still debated. Although a surgical strategy is said to be the best treatment option, some authors claim that medical treatment can be sufficient for some patients. Here we presented two cases of prosthetic valve endocarditis where both the patients were treated conservatively using multiple antibiotics. One patient improved within a short period of time, while another patient expired. University Heart Journal Vol. 12, No. 1, January 2016; 45-48